Legal Protection Of Underage E-Sports Players Related To Employment Agreements With E-Sports Companies - Muharrir Muharrir; Suhariningsih , Suhariningsih; Budi Santoso (CV. AFDIFAL MAJU BERKAH, 2024)
The purpose of this study was to be able to determine and analyze the legal protection arrangements for electronic sports players (E-Sports) that fall into the category of minors as it is known that children who are in their teens can not do much, therefore the employment agreement requires written permission of the parents. The author uses normative research methods, the nature of analytical prescriptive research. The results and discussion in this study concluded that legal protection for e-sports players with e-sports companies in principle work agreements have been preventively regulated in the law on sports, the Civil Code including special rules PBESI Regulation No. 034/PB-ESI/B/VI / 2021 as a form of regulation of E-sports legal protection in Indonesia. It's just that in terms of repressive legal protection through PBESI Regulation No. 034/PB-ESI/B/VI / 2021 regarding dispute resolution still contains weaknesses, as it is known that children before working ‘must obtain written permission from their parents and a work agreement is made with their parents’, while the regulation does not explain the involvement of parents in dispute resolution. Thus it is necessary to make changes to Article 43 paragraph (1) PBESI Regulation No. 034/PB-ESI/B/VI / 2021 on the implementation of E-sports activities in Indonesia.